Studi Kasus Asuhan Keperawatan Keluarga Penderita Hipertensi Dengan Gangguan Stres Pada Masa Pandemi Covid 19 Di Dusun Raos Baru Carat Gempol Pasuruan - Eka Diah Kartiningrum; Ajeng Fitria (MEDICA MAJAPAHIT, 2021)
This study aimed to examine the implementation of nursing care for families with hypertension with stress disorders during the Covid 19 pandemic in the Raos Baru Carat Gempol Pasuruan. This study used a case study design with 2 families as the observation unit that selected by purposive sampling method using certain inclusion criteria. The results showed that after the assessment on the families of Mr. K and Mr. M by using the family assessment format, interview method, observation and physical examination to add the necessary data, it showed that both patients said they did not dare to control or check for fear of contracting Covid-19. The results of the assessment with the DASS, obtained a score of Ny. S was 14 (mild stress) and Mrs. M was 16 (moderate stress). The perceived symptoms were difficulty sleeping, unable to relax, restless, irritable, irritable, easily irritated for trivial reasons. The difference between client 1 and 2 is in the family history of hypertension where client 1 has a family history of hypertension, the duration of suffering from hypertension was 20 years, while client 2 did not have a family history of hypertension, the age of client 1 was 51 years and client 2 was 56 years. The nursing diagnosis for both clients' families was stress that related to the family's inability to make decisions in carrying out appropriate actions to overcome family health problems. The intervention given to the families of the two clients was the same, because both families had the same problem and were carried out for 2 weeks. There was no difference in intervention between clients 1 and 2. The final evaluation results showed that the family had been able to practice deep breathing relaxation, transcendental meditation, and progressive muscle relaxation well, and had applied it every day until both clients seemed calmer and less anxious, more relaxed. and can sleep more soundly, both families are also willing to control the Puskesmas while still implementing health protocols according to the rules set by the government at the Puskesmas